(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Mishenina T. M. Technological approach to training in forming pedagogical competence of future teachers philological specialties. The article reveals the essence of the technological approach to learning in the process of didactic competence of future teachers of philological specialties. Disclosed the essential characteristics of didactic categories: educational content, the levels of assimilation of education, training situation, the learning activities. Given the description of the learning objectives, the types of educational content and levels of assimilation is an exhaustive list of possible targets and compounds of combinatorial types of educational content.